Global Airway Management of the Unstable Cervical Spine Survey - Stegmann, George Frederik (Department of Anaesthesia and Perioperative Medicine, 2022)
Background Rapid growth in optical and video devices for indirect visualisation of the airway has expanded the options for emergency and elective endotracheal intubation in patients with unstable fractures of the cervical spine. Aiming to ascertain whether video laryngoscopy (VL) has replaced awake flexible intubation (AFI) as the preferred technique for airway management, we conducted a global survey to evaluate current clinical practice. Methods After ethics approval, we created a questionnaire featuring one emergency and one urgent elective hypothetical patient with unstable injuries of the cervical spine. Target sample sizes per country were estimated using data from the World Federation of Societies of Anaesthesiologists' (WFSA) Global Anaesthesia Workforce Survey. Respondents were asked about their training, experience, airway skills, current clinical setting, and availability of airway equipment, as well as their preferred airway strategy in each case. The questionnaire was actively distributed for one year through the WFSA member societies and via social networks to physician anaesthesia providers (PAPs). Global and regional trends were assessed using descriptive statistics. Results Of a total of 1904 responses, 1153 (101 countries) were included in the final analysis. In the emergency case, 46.9% (95% confidence interval [CI]: 44.0–49.8%) of participants preferred VL and 39.8% (95% CI: 38.0-42.6%) chose AFI. In the urgent elective case, 51.3% (95% CI: 48.3-54.3%) selected VL as their preferred method, while 37.3% (95% CI: 34.4-40.2%) indicated AFI. Significant regional variations in preference were found. Conclusion The results suggest that practice in airway management of unstable cervical spine fractures is changing, and currently tends to favour VL over AFI. There is a statistically significant preference for VL in elective cases, traditionally considered to be a stronghold of AFI.